The HOG Pathway Is Critical for the Colonization of the Mouse Gastrointestinal Tract by Candida albicans - Prieto, Daniel; Román, Elvira; Correia, Inês; Pla, Jesus (PLOS ONE, 2014)
The opportunistic pathogen Candida albicans is a frequent inhabitant of the human gastrointestinal tract where it usually behaves as a harmless commensal. In this particular niche, it needs to adapt to the different micro environments that challenge its survival within the host. In order to determine those factors involved in gut adaptation, we have used a gastrointestinal model of colonization in mouse to trace the behaviour of fungal cells. We have developed a genetic labelling system based on the complementary spectral properties of the fluorescent proteins GFP and a new C. albicans codon-adapted RFP (dTOM2) that allow a precise quantification of the fungal population in the gut via standard in vitro cultures or flow cytometry. This methodology has allowed us to determine the role of the three MAP kinase pathways of C. albicans (mediated by the MAPK Mkc1, Cek1 or Hog1) in mouse gut colonization via competitive assays with MAPK pathway mutants and their isogenic wild type strain. This approach reveals the signalling through HOG pathway as a critical factor influencing the establishment of C. albicans in the mouse gut. Less pronounced effects for mkc1 or cek1 mutants were found, only evident after 2–3 weeks of colonization. We have also seen that hog1 mutants is defective in adhesion to the gut mucosa and sensitive to bile salts. Finally, we have developed a genetic strategy for the in vivo excision (tetracycline-dependent) of any specific gene during the course of colonization in this particular niche, allowing the analysis of its role during gut colonization.